PSIXOLOGIYALÍQ METODIKALARDÍ QAYTA ISLEWDE ZÁRÚRLI STATISTIKALÍQ MAǴLÍWMATLAR - Turdımuratova, A.; Turdımuratova, A. (SCIENCE and SOCIETY, 2024)
The article explains the significance of development, statistical data calculation methods, and the relevance of psychological techniques. It serves as a methodological guide written in Karakalpak and a valuable textbook on psychodiagnosis. The article provides simple examples of task difficulty index calculation and frequency analysis, which will be comprehensible to any novice psychodiagnostician. The concept of standardisation for calculating raw scores is described in detail.